When Do Gender Wage Differences Emerge? A Study of Azerbaijan's Labor Market - Francesco Pastore; Sarosh Sattar; Nistha Sinha; Erwin R. Tiongson (Institute for the Study of Labor (IZA), 2016)
Building on recent analyses that find a sizeable, overall gender wage gap in Azerbaijan's workforce, this paper uses data on young workers in their early years in the labor market to understand how gender wage gaps evolve over time, if at all. Using a unique database from a survey of young people age 15-29 years old, we provide evidence that new labor market entrants begin with little or no gender differences in earnings, but a wage gap gradually emerges over time closer to the childbearing years. The gender wage gap grows from virtually zero, or even a small, positive gap in favor of women, until the age of 20 years to about 20% two years later and even more than 30% at the age of 29 years. The gap in labor supply rises from almost zero to about 20% during the years from 19 to 22, while the gap in hours worked falls from positive (up to 6 hours per week more than their male counterparts) to negative (up to -5 hours per week) over the same period in the life cycle. When decomposing the gap at different deciles of the wage distribution, it appears that most of it is at the lower and upper end of the distribution, among young adults and the prime-age workers. Selection of women into employment is strong and strongly skill-based: when controlling for sample selection bias, the gender gap becomes positive.
Keywords: I21; J13; J15; J16; J24; J31; J7; P30; 330; gender wage gap and dynamics; early labor market outcomes; school-to-work transitions; earnings equations; decomposition analysis